Application of modern information technologies in prevention of corruptive practices in an organisation - Agata Stachowicz-Stanusch; Joanna Machnik-Slomka (Institute of Economic Research (IER), 2015)
The issue of corruption has recently become one of the most significant problems raised on the international scene. The discussion, currently conducted in different environments, places the issue of corruption in the centre of particular interest. In the world of research on corruption and its various forms there are multiple studies conducted by the representatives of different science disciplines. The researchers of management studies investigate corruption at both the individual and organizational level. The aspects of application of different methods and techniques by means of modern technologies are an important area of research on various aspects of corruption. The aim of the article is to analyse the possibility of application of modern tools in prevention of corrupting practices in an organization, particularly at the universities.
Keywords: A11; A13; M14; 330; corruption; corrupting practices; ethics; information technology